2022
DOI: 10.1177/87551225221116266
|View full text |Cite
|
Sign up to set email alerts
|

Complications of Corticosteroid Therapy: A Comprehensive Literature Review

Abstract: Relevance to Patient Care and Clinical Practice: Corticosteroids are among the most prescribed medications, particularly during the COVID-19 era. The literature has clearly highlighted the dangers of prolonged, high-dose corticosteroid use, which is important for clinicians to consider before treating patients in their clinical practices. Objective: The objective of this article is to review the literature on complications of corticosteroid use, review corticosteroid pharmacokinetics, and provide an updated re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 70 publications
0
4
0
Order By: Relevance
“…The group at highest risk of CS-induced cataracts was oral CS use for >5 years (OR 3.25; 95% CI 1.39 to 7.58). 15…”
Section: Discussionmentioning
confidence: 99%
“…The group at highest risk of CS-induced cataracts was oral CS use for >5 years (OR 3.25; 95% CI 1.39 to 7.58). 15…”
Section: Discussionmentioning
confidence: 99%
“…Corticosteroids, while potentially improving postoperative symptoms through their anti-inflammatory and immunosuppressive effects, can also lead to a variety of complications [ 18 20 ]. These complications can adversely affect the patient’s recovery.…”
Section: Methodsmentioning
confidence: 99%
“…While the consensus recommends high-dose oral steroids for anti-HMGCR IMNM, 2 there are concerns regarding potential complications such as hyperglycemia and psychiatric symptoms, 7 especially in older adults. 8,9 Induction without steroids may be successful in selected patients, especially in those without muscle weakness.…”
Section: Dear Editormentioning
confidence: 99%
“…1,5 Barnett et al reported that the number of disorders affecting an individual increases with age, and approximately 65% of those aged >65 years and almost 82% of those aged 85 years or older have multimorbidity. 7 There has been debate regarding the association between polypharmacy and renal function. Sakamoto et al (2020), in a study of cardiovascular outpatients, reported that polypharmacy was associated not only with poor renal function, but also with an accelerated deterioration of renal…”
Section: Number Of Medicines Taken Correlates With Renal Function In ...mentioning
confidence: 99%